Zu den ökologischen Metaphern bei Paulus - Najda, Andrzej (Studia Ecologiae et Bioethicae, 2005)
Many times in his letters Paul underlines that he is an apostle of Christ Jesus chosen, called and sent to proclaim the Gospel of God (cfr. Rom 1,1; 1 Cor 1,1; 2 Cor 1,1). In his teaching he willingly used different metaphors, among which those taken from the held of ecology had an important role. Paul makes use of them when speaks of the reality, the nature and the tasks of the Christian community (e.g.: Rom 7,4ff.; 9,21; 1 Cor 3,9), when he wants to describe his missionary activity or to express his apostolic consciousness (e.g.: 1 Cor 3,6; 3,10; 2 Cor 10,8; 13,10).